Comparison of weed control methods in rice in the rainy and dry seasons - García, Byron; Parrales, Leiver; Villón, Henry; Torres, Sinthya; Vera, José; Moyano, Gavin; Villamar, Mónica (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2024)
Integrated weed management strategies are crucial to reduce crop production costs. The objective was to compare weed control techniques according to their efficiency and profitability in rice cultivation during the rainy and dry seasons. It was carried out under the quasi-experimental modality with the Student's t-test under a descriptive research type. Structured questionnaires were administered to 70 rice farmers in the area. Weeds were identified in areas every 10 m² within the rice crop, 10 and 15 days after sowing. The efficiency (E) of weed management in rice crops was calculated by applying the formula . The results showed that manual weeding has a monthly frequency, being used both in the rainy season (40 %) and in the dry season (44 %). The frequency of herbicide application was adjusted to the crop stage in the rainy season (39 %) and in the dry season (46 %). The efficiency (E) using the mechanical method was below one month during the rainy and dry seasons, registering 43%. Manual weeding showed an E of 49 % in the rainy season and 42 % in the dry season for up to 30 days. The combination of herbicides: Metsulfuron-methyl + Quinclorac; pyrazosulfuron-ethyl + Quinclorac, exhibited an E greater than 80 %, for more than 30 days in both seasons. The highest profitability was in the rainy season, thus presenting mechanized control USD 0.09 in rainfall and USD 0.04 in drought, chemical control USD 0.09 in rainfall and USD 0.07 in drought, and manual weeding USD 0.10 in rainfall and USD 0.06 in drought, for every dollar spent during the cultivation of rice.